On the QCD phase diagram at finite chemical potential - Haas, Lisa Marie; Braun, Jens; Pawlowski, Jan M. (Arxiv, 2010)
We present results for the phase diagram of QCD with two massless quark flavours as obtained from a first-principles functional renormalisation group approach. In particular we compute order parameters for chiral symmetry breaking and quark confinement at vanishing and non-zero imaginary chemical potential. Our analytical and numerical results suggest a close relation between the chiral and the deconfinement phase transition. We discuss the properties of dual order parameters at imaginary and real chemical potential.